Guanidine-rich helical polypeptides bearing hydrophobic amino acid pendants for efficient gene delivery. (19th February 2021) - Yu, Zikun; Zhang, Zhimin; Yan, Jing; Zhao, Ziyin; Ge, Chenglong; Song, Ziyuan; Yin, Lichen; Tang, Haoyu
Abstract : Guanidine-rich helical polypeptides bearing hydrophobic amino acid pendants displayed high transfection efficiency both in vitro and in vivo and low cytotoxicity toward applications in gene therapy. Abstract : Non-viral gene delivery vectors with high transfection efficiency both in vitro and in vivo and low cytotoxicity are highly desirable for clinical applications. Herein, a series of guanidine-rich polypeptides bearing hydrophobic amino acid pendants was efficiently prepared via the 1, 3-dipolar cycloaddition between azido decorated polypeptide and propargyl functionalized guanidinium and N -acetylamino acids. CD analysis indicated α-helical conformations of all resulting polypeptides in aqueous solution. The guanidine-rich polypeptide/DNA complexes showed significantly enhanced cellular internalization and high cell viability (>90%) in different mammalian cell lines ( i.e., HeLa and RAW 264.7) at concentrations of the best performance. The top-performing guanidine-rich polypeptide containing 10% N -acetyl-l -valine pendants outperformed the commercial transfection reagent PEI by 400 times in vitro and 6 times in vivo . This study provides a new guidance for future molecular design of non-viral gene vectors with high delivery efficiency and low cytotoxicity.